STRATEGI PEMERINTAH DAERAH DALAM PENGELOLAAN PASAR TRADISIONAL BALANG-BALANG KABUPATEN GOWA - Arman; Junaedi; Ahmad Taufik; Ansyari Mone (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2020)
This article discusses the Regional Government Strategy in the Management of the Balang-Balang Traditional Market, Gowa Regencyknow the things that affect the local government strategy in the Management of the Balang-Balang Traditional Market, Gowa Regency. ApproachThe research used is descriptive qualitative. The data obtained from interviews, and observations were then analyzed by looking at the program strategylocal government in the management of the Balang-Balang market along with the inhibiting factors found in this study. As for the activities inData analysis in this study are: data reduction, data presentation, and drawing conclusions. The results show that there are programsOne of the activities carried out by the regional government is business development and trade facilities that highlight planning and revitalization effortsmarket, the Gowa Regency government's strategy is to prioritize the improvement of people's market facilities so that the process of improving facilities can operateprioritizing parking facilities which cause congestion problems in the road area near the market but achieving targets for price stabilityin traditional markets are well controlled. In the aspects of leadership, motivation and communication systems, it shows that there is a process of manager interactionthe market with the Department of Industry and Trade to check if there is a discrepancy in the procedure based on conditions that occur in the market and the formCommunication that is considered effective is that the market manager visits the Department of Industry and Trade to deposit market fees every yearweek as well as the reporting carried out explaining market conditions and aspects of human resource management, indicating that there are effortsTo improve market management capabilities, market heads are given training through Technical Guidance which aims to provide briefingknowledge in managing the market.